The migration and its effect on the learning of the english language with students at “unidad educativa anexa a la Universidad Nacional de Loja”. Academic period 2012 – 2013 - Armijos González, Pedro Orlando (2014)
The research work entitled: THE MIGRATION AND ITS EFFECT ON THE LEARNING OF THE ENGLISH LANGUAGE WITH STUDENTS AT “UNIDAD EDUCATIVA ANEXA A LA UNIVERSIDAD NACIONAL DE LOJA”. ACADEMIC PERIOD 2012 – 2013, has been developed to identify the effect that the family parents‘ migration causes on the English Language Learning. The Scientific Method was applied to discover the different characteristics of the research object. Additionally, as particular methods were used: the descriptive one, to describe the gathered data; and, the analytic – synthetic one, to analyze the obtained results. The survey was applied to the Teachers and Students and the interview to the Social Worker; the logical analysis processed the information and the descriptive statistics described the obtained results into graphs and tables. The most important findings are, that parents‘ migration causes a low performance, due to the familiar disintegration and lack of affection. Also, students show behavioral and attitudinal problems as consequence of their disciplinary and academic difficulties.